Ethnopharmacological Survey of Traditional Chinese Medicine Pharmacy Prescriptions for Dysmenorrhea - Su, Kuo-Han; Su, Shan-Yu; Ko, Chien-Yu; Cheng, Yung-Chi; Huang, Shyh-Shyun; Chao, Jung (Frontiers in Pharmacology, 2021)
Chinese herbal medicines have long been used for the treatment of dysmenorrhea. The treatment experiences of traditional Chinese medicine (TCM) pharmacies passed down through generations have contributed to a wealth of prescriptions for dysmenorrhea that have achieved significant therapeutic effects in countless Taiwanese women. Therefore, surveying and analyzing these prescriptions may enable us to elucidate the core medication combinations used in TCM prescriptions for dysmenorrhea. In the present study, a field investigation was conducted on various TCM pharmacies in Taiwan. A total of 96 TCM pharmacies were sampled, and 99 prescriptions for dysmenorrhea containing 77 different medicinal materials were collected. Compositae (8%) was the most common botanical source of the medicinal materials, and the predominant TCM property and flavor of the materials were warm (45%) and sweet (73%), respectively. The blood-activating and stasis-dispelling effect (23%) and the qi-tonifying effect (23%) were the most prevalent traditional effects, and the modern pharmacological effects most commonly found in the materials were anti-inflammatory (73%), antitumor (59%), and analgesic (12%) effects. Network analysis of the 77 medicinal materials used in the prescriptions, which was performed using the Traditional Chinese Medicine Inheritance Support System, yielded seven core medicinal materials and the corresponding network diagram. The seven core medicinal materials ranked in order of relative frequency of citation (RFC) were Angelica sinensis (Oliv.) Diels (Dang Gui), Ligusticum chuanxiong Hort (Chuan Qiong), Rehmannia glutinosa Libosch. (Di Huang), Paeonia lactiflora Pall. (Bai Shao), Hedysarum polybotrys Hand.-Mazz (Hong Qi), Lycium chinense Mill. (Gou Qi Zi), and Cinnamomum cassia (L.) J. Presl (Gui Zhi). A total of 58 combinations, each consisting of two to five of the seven medicinal materials and 107 association rules among the materials, were identified. This study provides a record of valuable knowledge on TCM pharmacy prescriptions for dysmenorrhea. The rich medicinal knowledge of TCM pharmacies in Taiwan is worthy of further exploration, and the results of this study can serve as a basis for future pharmacological research and the development of naturally derived medications for dysmenorrhea.